Integrated groundwater noble gas and isotope tracers constrain hydroclimate variability and subsurface volatile sources - Grace A. Brown; Andrew J. Love; Eddie W. Banks; Michael W. Broadley; Rebecca L. Tyne; Thomas E. Chambers; Alec Deslandes; Axel Suckow; Israela Musan; Kevin L. Cahill; William J. Jenkins; Alan M. Seltzer (Earth and Planetary Science Letters, 2026)

Soil organic matter stabilization varies with nitrogen enrichment and hydrogeomorphic setting in a marsh–mangrove ecotone - Mercedes M. Pinzon; Jocelyn Bravo; Samantha K. Chapman; J. Adam Langley; Lisa G. Chambers (Science of The Total Environment, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Evaluating psychological accounts of diet-related mood improvements using novel control conditions - Leah M. Dudley; Richard J. Stevenson; Alexandra Mruk; Milena Gandy; Jaime R. Chambers; Heather M. Francis (Appetite, 2026)

Benzene exposure biomarkers are associated with recently smoking tobacco and pumping gasoline in the U.S. population aged 12 and over: NHANES 2017–March 2020 - Brandon M. Kenwood; Can Zhang; David M. Chambers; Wanzhe Zhu; Benjamin C. Blount; Lanqing Wang (Environmental Research, 2026)

The carbon dynamic and driving mechanisms of peatland in the Changbaishan volcanic field of China - Mingming Zhang; Wenkai Liu; Li Wang; Frank M. Chambers (CATENA, 2026)

Changing volatile emissions and sources along the Ethiopian Rift - Abate A. Melaku; Gemechu B. Teferi; Takele Mihretie; Snorri Gudbrandsson; Yared Sinetebeb; Peter H. Barry; Tobias P. Fischer; Finlay M. Stuart; Ugur Balci; Sæmundur A. Halldórsson; Chris J. Ballentine; Darren J. Hillegonds; et al. (Earth and Planetary Science Letters, 2026)

Relationships among peri-traumatic circulating endocannabinoids and long-term, negative outcomes following traumatic injury - Emily A. Albertina; Carissa W. Tomas; Timothy J. Geier; Sydney C. Timmer-Murillo; Isela G. Pina; Kelley Jazinski-Chambers; Garrett Sauber; Jacklynn M. Fitzgerald; Christine L. Larson; Terri A. deRoon-Cassini; Cecilia J. Hillard (Psychopharmacology, 2026)
Rationale Traumatically injured individuals can develop chronic negative psychological sequelae. Improved understanding of contributing, peri-traumatic risk factors is essential to reduce the risk of these consequences. Previous studies have found that peri-traumatic, circulating endocannabinoid concentrations are positively associated with development of post-traumatic stress disorder (PTSD), chronic pain and depression months later, particularly in members of racial/ethnic groups that have been historically marginalized. Objectives This replication study examined relationships among peri-trauma serum endocannabinoid concentrations and long-term consequences in a cohort comprised primarily of individuals from marginalized racial and ethnic groups. Methods Participants ( n = 100; 81% from marginalized racial and ethnic groups) were traumatically injured adults presenting to the ED of an urban tertiary care hospital. Endocannabinoids N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) were measured in serum collected within days (peri-trauma) and 6–10 months following injury (follow-up). Assessments, including PTSD, depression, pain and quality of life were completed. Statistical approaches, including multivariate, hierarchical regressions, were used to determine associations among serum endocannabinoid concentrations and long-term outcomes. Results Although it did not survive correction for multiple comparisons, peri-trauma serum 2-AG concentrations. Peri-trauma serum 2-AG concentrations were also positively associated with PTSD, pain severity, and functional engagement scores at follow-up. There were no significant associations between circulating 2-AG or AEA and depression. Conclusions These findings generally replicate earlier studies demonstrating that serum 2-AG concentrations are biomarkers of risk for PTSD and pain and uncover an additional association with poor functional quality of life. Further studies are needed to determine the underlying mechanisms of these relationships.

Complete genome sequence of citrus tristeza virus isolate PB61, a commercially deployed mild strain for cross-protection in grapefruit - M. A. Jackson; D. B. Kidanemariam; G. A. Chambers; A. Englezou; A. D.W. Geering; N. J. Donovan (Australasian Plant Pathology, 2026)
Citrus tristeza virus (CTV; species Closterovirus tristezae ) is ubiquitous in Australia, occurring in all production areas. Stem-pitting disease in white grapefruit varieties caused by CTV is managed by mild strain cross-protection. However, the protective isolate of CTV used for cross-protection, labelled PB61, is not fully characterised at the molecular level, even though most grapefruit budwood is inoculated with this virus isolate before release. In this study, we employed high throughput sequencing to assemble the 19,254 nucleotide-long genome of virus isolate PB61. Phylogenetic analysis revealed that PB61 belongs to the resistance-breaking (RB) genotype group first identified in New Zealand. PB61 is the first CTV isolate of any genotype from Australia to be sequenced in entirety, and the generation of this data provides a foundation for better understanding the mechanism of cross-protection in grapefruit.

Multivariate environmental and trait-based controls of transpiration in the Central Amazon Rainforest - Yilin Fang; Cristina Santos da Silva; Adam Collins; Bruno O. Gimenez; Kolby Jardine; Robinson I. Negrón-Juárez; Regison Oliveira; Valdiek da Silva Menezes; Kurt Solander; Gustavo Spanner; Jeffrey M. Warren; Cynthia L. Wright; et al. (Agricultural and Forest Meteorology, 2026)

The non-autogenic carbon accumulation process in a peatland of the Changbai Mountains and its response to climate changes during the Late Holocene - Wenkai Liu; Mingming Zhang; Frank M. Chambers; Yuzhu Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Small fish, big implications: considerations for an ecosystem approach to capelin fisheries management - Warsha Singh; John T. Trochta; Hannah M. Murphy; David W. McGowan; Aaron T. Adamack; Mayumi L. Arimitsu; Birkir Barðarson; Höskuldur Björnsson; Bjarte Bogstad; Mathieu Boudreau; Catherine Chambers; Harald Gjøsæter; et al. (Reviews in Fish Biology and Fisheries, 2025)

Endocrine Disrupting Chemicals in Human Milk: A Systematic Review of Concentrations and Potential Health Implications - Fiona Dunn; Hannah Sullivan; Megan Romano; Christina D. Chambers; Joseph M. Braun; Katherine E. Manz (Current Environmental Health Reports, 2025)
Purpose of Review Endocrine-disrupting chemicals (EDCs) disrupt the synthesis, transport, action, or metabolism of endogenous hormones in the human body. EDCs often enter the body through inhalation, ingestion, or dermal contact and can accumulate in the body. Remobilization or transfer of EDCs can occur during lactation, causing human milk to become contaminated with a variety of EDCs, which could expose nursing infants and children to these chemicals. Recent Findings Several studies have examined the concentration ranges for one or multiple EDC(s) in human milk. Additional studies document associations between EDC exposure and adverse health outcomes, many of which are in adult populations. It is therefore essential to understand the extent to which EDCs in human milk contribute to cumulative early-life exposures. Summary We performed a literature review of peer-reviewed studies reporting concentrations of one or more of the following EDCs in human milk during or after 2004: bisphenols, organochlorine pesticides (OCPs), polycyclic aromatic hydrocarbons (PAHs), parabens, polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), per- and polyfluoroalkyl substances (PFAS), and phthalates. We identified concentration ranges for each chemical detected in human milk and health impacts associated with early-life exposures to EDCs noted across studies from this review. Determining the presence of EDCs in human milk and the associated effects of exposure through nursing is essential to develop feeding recommendations that safeguard infant and child health.

Genetic and serological analyses of equine influenza viruses isolated in Kumamoto and Hokkaido, Japan in 2025 - Manabu Nemoto; Nanako Kawanishi; Ryutaro Kamei; Kotaro Furusho; Kyoko Kawauchi; Yukiko Yabuuchi; Yasuhiro Oue; Yuko Uchida; Hayate Nishiura; Stephanie E. Reedy; Thomas M. Chambers; Feng Li; et al. (Veterinary Microbiology, 2025)

Nitrate contamination in New Zealand's domestic drinking water with a focus on rural groundwater-sourced self-supplies - Karyne M. Rogers; Diane Bradshaw; Phil Scadden; Conny Tschritter; Stuart Sanderson; Jannine Cooper; Andy Phillips; Jennifer Pannell; Juliane Thern; Steve Abel; Michael K. Joy; Xing Liu; et al. (Science of The Total Environment, 2025)

A spatially resolved and lipid-structured model for macrophage populations in early human atherosclerotic lesions - Keith L. Chambers; Mary R. Myerscough; Michael G. Watson; Helen M. Byrne (Journal of Theoretical Biology, 2025)

Generation of canine gallbladder cholangiocyte organoids from healthy and gallbladder mucocele patient dogs for functional analysis of anion channels - Itsuma Nagao; Hirotaka Tomiyasu; Yuko Goto-Koshino; Kota Nakase; Takumi Tsuruta; Yuto Namiki; Ryuichiro Sato; Yu Takahashi; Yuko Hashimoto; Yosuke Takahashi; Naohiro Takahashi; James K. Chambers; et al. (The Veterinary Journal, 2025)

Antibacterial marinopyrroles and pseudilins act as protonophores - Chambers C. Hughes; Gabriel Castro-Falcón; Jan Straetener; Jan Bornikoel; Daniela Reimer; Trevor N. Purdy; Anne Berscheid; Florence M. Schempp; Dennis Y. Liu; Roger G. Linington; Heike Brötz-Oesterhelt (Phytochemistry Letters, 2025)

Identifying the Nutrition Education Needs Among Early Interventionists in Tennessee - M. Johnson; K. Chambers; A. Chroust; M. Lee (Journal of the Academy of Nutrition and Dietetics, 2025)

Non-native grass invasion drives biodiversity loss after a single fire in a semi-arid shrubland - Adam L. Mahood; Jennifer K. Balch; David M. Barnard; Katherine N. Suding; Jeanne C. Chambers (Biological Conservation, 2025)

Resilience and vulnerability of the stonefly Nemoura cinerea to increased temperature and drought - Elmar Becker; J. Arie Vonk; Ralf C. M. Verdonschot; Jelmer Klaassen; Charlotte J. Chambers Moreira; Piet F. M. Verdonschot; Michiel H. S. Kraak (Aquatic Sciences, 2025)
Aquatic ecosystems worldwide are under severe pressure from climate change. However, studies on climate change effects on stream biota mainly focus on indicator or vulnerable species, leaving unanswered how more resilient species cope with elevated temperatures and drought, and the long-term consequences for these populations. This study therefore aims to determine the long-term population responses of a common, apparently less sensitive, aquatic insect to climate change-induced heat and drought and to unravel the mechanisms underlying its persistence under such harsh conditions. The long-term population responses of the stonefly Nemoura cinerea (Plecoptera: Nemouridae) to heat and drought are assessed by linking antecedent seasonal meteorological data to 42 years of abundance data from streams in the Netherlands. The mechanisms of resilience that enable N. cinerea to withstand these stressors during its transition from juvenile to adult stages are studied in a microcosm experiment on late-stage nymphs. Results from modelling long-term population responses to antecedent climate variables and observed responses in experimental microcosms show that temperature, and to a lesser extent drought, have negative impacts on N. cinerea fitness and abundance. Nonetheless, the species’ abundance has still modestly increased over the last four decades. This discrepancy may result from general water quality improvements, an increase in intermittent sites or altered biotic interactions due to increased intermittency, reducing competition and predation by less resilient species. Thus, even species apparently less sensitive to climate change experience harmful effects, though these appear to be offset by altered biotic and abiotic conditions.

P30-52 TempO-LINC single-cell transcriptomics assay sensitively resolves cellular heterogeneity and elucidates mechanisms of toxicity - S. Camiolo; D. Eastburn; K. White; N. Jayne; D. Gallegos; B. Robinette; B. Chambers; M. Campbell; S. Martos; D. Bell; B. Chorley; I. Shah; et al. (Toxicology Letters, 2025)

Optimizing woody fuel treatments to reduce wildfire risk to sagebrush ecosystems in the Great Basin of the western US - Michelle A. Day; Claire M. Tortorelli; Lisa M. Ellsworth; Karen C. Short; Jessi L. Brown; Sofia Koutzoukis; Julia Olszewski; Alan A. Ager; Jeanne C. Chambers (Journal of Environmental Management, 2025)

A New Zealand freshwater nitrate data quality validation study using commercial laboratories and portable testing instruments - Karyne M. Rogers; Conny Tschritter; Diane Bradshaw; Steve Abel; Jennifer L. Pannell; Juliane Thern; Tyler Heath; Phoebe Tio; Xing Liu; Laura Buckthought; Michael K. Joy; Peter Trolove; et al. (Chemosphere, 2025)

Field measurements of steelhead trout Oncorhynchus mykiss distribution, swimming behavior and response to water current exposure in a sea cage - M. Chambers; M. Doherty; M. Coogan; C. Rillahan; J. DeCew; P. Lader; W.H. Howell (Aquaculture, 2025)

Pressure management strategies for large-scale aquifer recharge: Mitigating the potential for injection-induced earthquakes - Ethan W. Conley; Cameron R. Chambers; John B. Ogunleye; Lars W. Koehn; Dan Holloway; Jamie Heisig-Mitchell; Martin Chapman; Mahesh Parija; Ryan M. Pollyea (Journal of Hydrology, 2025)

Human endothelial colony forming cells (ECFCs) require endothelial protein C receptor (EPCR) for cell cycle progression and angiogenic activity - Sarah E. J. Chambers; Jasenka Guduric-Fuchs; Edoardo Pedrini; Pietro M. Bertelli; Chutima Charoensuk; Elisa Peixoto; Varun Pathak; Hamza I. Alhamdan; Ruoxiao Xie; Anna Krasnodembskaya; Judith Lechner; Alan W. Stitt; et al. (Angiogenesis, 2025)
Vascular repair and regeneration are critical for tissue homeostasis. Endothelial colony forming cells (ECFCs) are vessel-resident progenitors with vasoreparative capacity and they offer an important avenue for allogeneic cytotherapy to achieve perfusion of ischemic tissues. Endothelial Protein C Receptor (EPCR) has been proposed as a marker for vascular endothelial stem cells, but its precise role in ECFC biology remains unknown. The current study has investigated the biological relevance of EPCR in ECFC function. Our data show that over 95% of ECFCs exhibit high EPCR expression. These levels surpassing CD34 and CD157, positions EPCR as a new robust ECFC immunophenotypic marker, alongside established markers CD31 and CD105. Functionally, depleting EPCR expression in ECFCs significantly diminished angiogenic activity, including proliferation, migration and tube formation. This knockdown also altered normal ECFC barrier function. Transcriptomic analysis indicated that knockdown of EPCR led to enrichment of gene signatures for cell cycle, TGF beta, and focal adhesion kinases. G1 cell cycle arrest was confirmed in ECFCs with depleted EPCR. Mechanistically, EPCR knockdown led to increased release of TGFβ2 and SMAD2/3 activation, coupled with increased p21, decreased pFAK, and increased transgelin. Additionally, we showed that quiescent ECFCs showed significantly lower EPCR expression when compared to proliferating ECFCs. In agreement with this, cell sorting experiments demonstrated that ECFCs with the highest EPCR expression exhibited the highest clonogenic capacity. In summary, our findings highlight that EPCR expression in ECFCs is critical for their angiogenic activity, by modulating cell cycle progression. Graphical abstract

Distributed acoustic sensing (DAS) for longwall coal mines - Derrick Chambers; Alexander Ankamah; Ahmad Tourei; Eileen R. Martin; Tim Dean; Jeffery Shragge; John A. Hole; Rafal Czarny; Gareth Goldswain; Jako du Toit; M. Shawn Boltz; James McGuiness (International Journal of Rock Mechanics and Mining Sciences, 2025)

The pull vs push approach to building climate change adaptive capacity: does innovation matter - Dina M. Abdelzaher; Angie Abdel Zaher; Silvana Chambers (Climate and Development, 2025)

Impact of manure and artificial fertilizer application on metal and metalloid distributions in agricultural soils and crops - M. Felipe-Sotelo; M. Brandtner; N.I. Ward; M. Al Sid Cheikh; M.A. Chambers; G. Rab; A. Cabal Rosel; M. Woegerbauer; M.M. Hassan; R. La Ragione; T. Tenson; V. Kisand; et al. (Chemosphere, 2025)

Assessment of Elemental Deficiency of Crossbred Dairy Cows and Mineral Composition in Natural Feed and Nutritional Supplements in the Northern and Northwestern Provinces in Sri Lanka - Joseph W. Clarkson; Neil I. Ward; Joaquín M. Prada; David Tisdall; Mónica Felipe-Sotelo; J. K. Vidanarachchi; Mike Christian; Mark Andrew Chambers (Biological Trace Element Research, 2025)
This study assessed the elemental status of cross-bred dairy cows in small holder farms in Sri Lanka, with the aim to establish the elemental baseline and identify possible deficiencies. For this purpose, 458 milk, hair, serum and whole blood samples were collected from 120 cows in four regions of Northern and Northwestern Sri Lanka, (namely Vavaniya, Mannar, Jaffna and Kurunegala). Farmers also provided a total of 257 samples of feed, which included local fodder as well as 79 supplement materials. The concentrations of As, Ca, Cd, Co, Cr, Cu, Fe, I, K, Mg, Mn, Mo, Na, Ni, Pb, Se, V and Zn were determined by inductively coupled plasma mass spectrometry (ICP-MS). Evaluation of the data revealed that all cows in this study could be considered deficient in I and Co (18.6–78.5 µg L −1 I and 0.06–0.65 µg L −1 Co, in blood serum) when compared with deficiency upper boundary levels of 0.70 µg L −1 Co and 50 µg L −1 I. Poor correlations were found between the composition of milk or blood with hair, which suggests that hair is not a good indicator of mineral status. Most local fodders meet dietary requirements, with Sarana grass offering the greatest nutritional profile. Principal component analysis (PCA) was used to assess differences in the elemental composition of the diverse types of feed, as well as regional variability, revealing clear differences between forage, concentrates and nutritional supplements, with the latter showing higher concentrations of non-essential or even toxic elements, such as Cd and Pb.

Investigation of adsorption parameters of saxitoxin onto loblolly pine-derived biochar synthesized at various pyrolysis temperature - Cadianne Chambers; Savannah Grimes; Russell C. Smith; Ayden Weil; M. Toufiq Reza (Chemosphere, 2025)

Corrigendum to “BCL-3 loss sensitises colorectal cancer cells to DNA damage by targeting homologous recombination” [DNA Repair 115 (2022) 103331] - Christopher Parker; Adam C. Chambers; Dustin J. Flanagan; Jasmine Wing Yu Ho; Tracey J. Collard; Greg Ngo; Duncan M. Baird; Penny Timms; Rhys G. Morgan; Owen J. Sansom; Ann C. Williams (DNA Repair, 2025)

Climate-driven peatlands development and vegetation dynamics in Northeastern China since the mid-Holocene: New evidence from Huanan peatlands - Yutong Qian; Dongmei Jie; Honghao Niu; Guizai Gao; Frank M. Chambers; Ziping Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Implications of Climatic Drying on the Aquatic Habitat and Aestivation Sites of an Endemic Freshwater Turtle - Anthony Santoro; Stephen J. Beatty; Jane M. Chambers; Brendan C. Ebner (Wetlands, 2024)

Net Present Value Calculations for Mining Post-Closure Financial Assurance - David M. Chambers (Mine Water and the Environment, 2024)
Most regulatory jurisdictions now require financial assurance for mines for post-closure activities, which typically include long-term monitoring and maintenance, and most importantly post-closure water treatment. Critical choices in calculating post-closure financial assurance include using a reputable cost estimation model to establish the amount needed for reclamation, selecting a realistic net return-on-investment for post-closure trust funds, and choosing the period of time over which the net present value calculation of the financial assurance is based. A conservative estimate of the amount of financial assurance is warranted to protect the public from assuming these costs. However, some regulatory agencies use financial assurance estimate practices that are arbitrary. The data and procedures needed to analyze and recommend conservative net present value calculations are readily available, but in too many instances are not being utilized.

Evaluation of an experimental kelp farm’s structural behavior using regression modelling and response amplitude operators derived from in situ measurements - Zachary Moscicki; M. Robinson Swift; Tobias Dewhurst; Michael MacNicoll; David W. Fredriksson; Michael Chambers; Igor Tsukrov (Ocean Engineering, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Corrigendum to “Four-dimensional electrical resistivity imaging for monitoring pumping-induced saltwater intrusion in a coastal aquifer” [Sci. Total Environ. Volume 867 (2023) 161442] - Mark C. McDonnell; Raymond Flynn; Jesús Fernández Águila; Gerard A. Hamill; Shane Donohue; Eric M. Benner; Christopher Thomson; Georgios Etsias; Thomas S.L. Rowan; Paul B. Wilkinson; Philip I. Meldrum; Jonathan E. Chambers (Science of The Total Environment, 2024)

Design, deployment, and operation of an experimental offshore seaweed cultivation structure - Zachary Moscicki; M. Robinson Swift; Tobias Dewhurst; Michael MacNicoll; Michael Chambers; Igor Tsukrov; David W. Fredriksson; Peter Lynn; Melissa E. Landon; Beth Zotter; Noah MacAdam (Aquacultural Engineering, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Determining subsurface temperature & lithospheric structure from joint geophysical-petrological inversion: A case study from Ireland - Emma L. Chambers; Raffaele Bonadio; Javier Fullea; Sergei Lebedev; Yihe Xu; Duygu Kiyan; Christopher J. Bean; Patrick A. Meere; Ben Mather; Brian M. O'Reilly (Tectonophysics, 2023)

Nature-based solutions for leveed river corridors - Matthew L. Chambers; Charles B. van Rees; Brian P. Bledsoe; David Crane; Susana Ferreira; Damon M. Hall; Rod W. Lammers; Craig E. Landry; Donald R. Nelson; Matt Shudtz; Burton C. Suedel (Anthropocene, 2023)

The Impact of Homestyles-2 Nutrition Education Curriculum on Family Mealtime Behaviors, Supports, and Perceptions of Parents/Caregivers of Children Ages 6 to 11 - J. Zeldman; I. Ramirez; K. Chambers; L. Brunson; Y. Li; L. O'Neal; M. Olfert; C. Byrd-Bredbenner; K. Shelnutt (Journal of the Academy of Nutrition and Dietetics, 2023)

Adolescents’ Knowledge of Myplate as It Relates to Their Consumption of Fruits, Vegetables, and Whole Grains - M. Badolato; A. Mathews; K. Shelnutt; L. House; K. Chambers; J. Colee (Journal of the Academy of Nutrition and Dietetics, 2023)

A Spatial Model Comparing Above- and Belowground Blue Carbon Stocks in Southwest Florida Mangroves and Salt Marshes - Kara R. Radabaugh; Ryan P. Moyer; Amanda R. Chappel; Joshua L. Breithaupt; David Lagomasino; Emma E. Dontis; Christine E. Russo; Brad E. Rosenheim; Lisa G. Chambers; Elitsa I. Peneva-Reed; Joseph M. Smoak (Estuaries and Coasts, 2023)

An Improved Framework for Estimating Organic Carbon Content of Mangrove Soils Using loss-on-ignition and Coastal Environmental Setting - Joshua L. Breithaupt; Havalend E. Steinmuller; Andre S. Rovai; Kevin M. Engelbert; Joseph M. Smoak; Lisa G. Chambers; Kara R. Radabaugh; Ryan P. Moyer; Amanda Chappel; Derrick R. Vaughn; Thomas S. Bianchi; Robert R. Twilley; et al. (Wetlands, 2023)
The use of loss on ignition (LOI) measurements of soil organic matter (SOM) to estimate soil organic carbon (OC) content is a decades-old practice. While there are limitations and uncertainties to this approach, it continues to be necessary for many coastal wetlands researchers and conservation practitioners without access to an elemental analyzer. Multiple measurement, reporting, and verification (MRV) standards recognize the need (and uncertainty) for using this method. However, no framework exists to explain the substantial differences among equations that relate SOM to OC; consequently, equation selection can be a haphazard process leading to widely divergent and inaccurate estimates. To address this lack of clarity, we used a dataset of 1,246 soil samples from 17 mangrove regions in North, Central, and South America, and calculated SOM to OC conversion equations for six unique types of coastal environmental setting. A framework is provided for understanding differences and selecting an equation based on a study region’s SOM content and whether mineral sediments are primarily terrigenous or carbonate in origin. This approach identifies the positive dependence of conversion equation slopes on regional mean SOM content and indicates a distinction between carbonate settings with mean (± 1 S.E.) OC:SOM of 0.47 (0.002) and terrigenous settings with mean OC:SOM of 0.32 (0.018). This framework, focusing on unique coastal environmental settings, is a reminder of the global variability in mangrove soil OC content and encourages continued investigation of broadscale factors that contribute to soil formation and change in blue carbon settings.

Improving data collection in pregnancy safety studies: Towards standardization of data elements in pregnancy reports from public and private partners (ConcePTION) - Guillaume Favre; Jonathan L. Richardson; Alan Moore; Yvonne Geissbühler; Valentine Jehl; Alison Oliver; Svetlana Shechtman; Orna Diav-Citrin; Maya Berlin; Tal De-Haan; Anil Mor; Meritxell Sabidó; et al. (Neurotoxicology and Teratology, 2023)

4D electrical resistivity to monitor unstable slopes in mountainous tropical regions: an example from Munnar, India - Arnaud Watlet; Hemalatha Thirugnanam; Balmukund Singh; Nitin Kumar M.; Deepak Brahmanandan; Cornelia Inauen; Russell Swift; Phil Meldrum; Sebastian Uhlemann; Paul Wilkinson; Jonathan Chambers; Maneesha Vinodini Ramesh (Landslides, 2023)
The number of large landslides in India has risen in the recent years, due to an increased occurrence of extreme monsoon rainfall events. There is an urgent need to improve our understanding of moisture-induced landslide dynamics, which vary both spatially and temporally. Geophysical methods provide integrated tools to monitor subsurface hydrological processes in unstable slopes at high spatial resolution. They are complementary to more conventional approaches using networks of point sensors, which can provide high temporal resolution information but are severely limited in terms of spatial resolution. Here, we present and discuss data from an electrical resistivity tomography monitoring system—called PRIME—deployed at the Amrita Landslide Early Warning System (Amrita-LEWS) site located in Munnar in the Western Ghats (Kerala, India). The system monitors changes in electrical resistivity in the subsurface of a landslide-prone slope that directly threatens a local community. The monitoring system provides a 4D resistivity model informing on the moisture dynamics in the subsurface of the slope. Results from a 10-month period spanning from pre-monsoon to the end of the monsoon season 2019 are presented and discussed with regard to the spatial variation of soil moisture. The temporal changes in resistivity within the slope are further investigated through the use of time-series clustering and compared to weather and subsurface pore water pressure data. This study sheds new light on the hydrological processes occurring in the shallow subsurface during the monsoon and potentially leading to slope failure. This geophysical approach aims at better understanding and forecasting slope failure to reduce the risk for the local community, thereby providing a powerful tool to be included in local landslide early warning systems.

A new lipid-structured model to investigate the opposing effects of LDL and HDL on atherosclerotic plaque macrophages - Keith L. Chambers; Mary R. Myerscough; Helen M. Byrne (Mathematical Biosciences, 2023)

Antigenic comparison of H3N8 equine influenza viruses belonging to Florida sublineage clade 1 between vaccine strains and North American strains isolated in 2021–2022 - Manabu Nemoto; Stephanie E. Reedy; Takanori Yano; Kenya Suzuki; Shino Fukuda; Marie Garvey; Yoshinori Kambayashi; Hiroshi Bannai; Koji Tsujimura; Takashi Yamanaka; Ann Cullinane; Thomas M. Chambers (Archives of Virology, 2023)

Stream macroinvertebrate community responses to an agricultural gradient alter consumer-driven nutrient dynamics - Heather A. Loomer; Karen A. Kidd; Maitane Erdozain; Glenn A. Benoy; Patricia A. Chambers; Joseph M. Culp (Hydrobiologia, 2023)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Stem respiration and growth in a central Amazon rainforest - Kolby J. Jardine; Leticia O. Cobello; Liliane M. Teixeira; Malyia-Mason S. East; Sienna Levine; Bruno O. Gimenez; Emily Robles; Gustavo Spanner; Charlie Koven; Chongang Xu; Jeffrey M. Warren; Niro Higuchi; et al. (Trees, 2022)

The Effect of Marsh Age on Ecosystem Function in a Rapidly Transgressing Marsh - Amy K. Langston; Daniel J. Coleman; Nathalie W. Jung; Justin L. Shawler; Alexander J. Smith; Bethany L. Williams; Serina S. Wittyngham; Randolph M. Chambers; James E. Perry; Matthew L. Kirwan (Ecosystems, 2022)

Population growth dynamics and their implications for fish welfare in mixed-size cohorts of Cyprinus Carpio var koi grown in a commercial-scale aquaponics system - Danielle M. Maitland; Joe Baker; Greg Chambers; Neil W. Ross; Stefanie M. Colombo (Aquaculture International, 2022)

Substantial long‐term loss of alpha and gamma diversity of lake invertebrates in a landscape exposed to a drying climate - S. T. Atkinson; D. Cale; A. Pinder; J. M. Chambers; S. A. Halse; Belinda J. Robson (Global Change Biology, 2021)
Many regions across the globe are shifting to more arid climates. For shallow lakes, decreasing rainfall volume and timing, changing regional wind patterns and increased evaporation rates alter water regimes so that dry periods occur more frequently and for longer. Drier conditions may affect fauna directly and indirectly through altered physicochemical conditions in lakes. Although many studies have predicted negative effects of such changes on aquatic biodiversity, empirical studies demonstrating these effects are rare. Global warming has caused severe climatic drying in southwestern Australia since the 1970s, so we aimed to determine whether lakes in this region showed impacts on lake hydroperiod, water quality, and α, β and γ diversity of lake invertebrates from 1998 to 2011. Seventeen lakes across a range of salinities were sampled biennially in spring in the Wheatbelt and Great Southern regions of Western Australia. Multivariate analyses were used to identify changes in α, β and γ diversity and examine patterns in physicochemical data. Salinity and average rainfall partially explained patterns in invertebrate richness and assemblage composition. Climatic drying was associated with significant declines in lake depth, increased frequency of dry periods, and reduced α and γ diversity (γ declined from ~300 to ~100 taxa from 1998 to 2011 in the 17 wetlands). In contrast, β diversity remained consistently high, because each lake retained a distinct fauna. Mean α diversity per‐lake declined both in lakes that dried and lakes that did not dry out, but lakes which retained a greater proportion of their maximum depth retained more α diversity. Accumulated losses in α diversity caused the decline in γ diversity likely through shrinking habitat area, fewer stepping stones for dispersal and loss of specific habitat types. Biodiversity loss is thus likely from lakes in drying regions globally. Management actions will need to sustain water depth in lakes to prevent biodiversity loss.

An agenda for research and action toward diverse and just futures for life on Earth - C. Wyborn; J. Montana; N. Kalas; S. Clement; F. Davila; N. Knowles; E. Louder; M. Balan; J. Chambers; L. Christel; T. Forsyth; G. Henderson; et al. (Conservation Biology, 2021)
Decades of research and policy interventions on biodiversity have insufficiently addressed the dual issues of biodiversity degradation and social justice. New approaches are therefore needed. We devised a research and action agenda that calls for a collective task of revisiting biodiversity toward the goal of sustaining diverse and just futures for life on Earth. Revisiting biodiversity involves critically reflecting on past and present research, policy, and practice concerning biodiversity to inspire creative thinking about the future. The agenda was developed through a 2‐year dialogue process that involved close to 300 experts from diverse disciplines and locations. This process was informed by social science insights that show biodiversity research and action is underpinned by choices about how problems are conceptualized. Recognizing knowledge, action, and ethics as inseparable, we synthesized a set of principles that help navigate the task of revisiting biodiversity. The agenda articulates 4 thematic areas for future research. First, researchers need to revisit biodiversity narratives by challenging conceptualizations that exclude diversity and entrench the separation of humans, cultures, economies, and societies from nature. Second, researchers should focus on the relationships between the Anthropocene, biodiversity, and culture by considering humanity and biodiversity as tied together in specific contexts. Third, researchers should focus on nature and economies by better accounting for the interacting structures of economic and financial systems as core drivers of biodiversity loss. Finally, researchers should enable transformative biodiversity research and action by reconfiguring relationships between human and nonhuman communities in and through science, policy, and practice. Revisiting biodiversity necessitates a renewed focus on dialogue among biodiversity communities and beyond that critically reflects on the past to channel research and action toward fostering just and diverse futures for human and nonhuman life on Earth.

Evaluating a Steady-State Model of Soil Accretion in Everglades Mangroves (Florida, USA) - Randolph M. Chambers; Adrianna L. Gorsky; Edward Castañeda-Moya; Victor H. Rivera-Monroy (Estuaries and Coasts, 2021)

Fruit and seed traits of native and invasive plant species in Hawai‘i: implications for seed dispersal by non-native birds - Jinelle H. Sperry; Dylan O’Hearn; Donald R. Drake; Amy M. Hruska; Samuel B. Case; Jeferson Vizentin-Bugoni; Clint Arnett; Tim Chambers; Corey E. Tarwater (Biological Invasions, 2021)

Quantifying the contribution of matric suction on changes in stability and displacement rate of a translational landslide in glaciolacustrine clay - K. Sattler; D. Elwood; M. T. Hendry; D. Huntley; J. Holmes; P. B. Wilkinson; J. Chambers; S. Donohue; P. I. Meldrum; R. Macciotta; P. T. Bobrowsky (Landslides, 2021)

Characterization of US population levels of urinary methylcarbamoyl mercapturic acid, a metabolite of N,N-dimethylformamide and methyl isocyanate, in the National Health and Nutrition Examination Survey (NHANES) 2005–2006 and 2011–2016 - Brandon M. Kenwood; Pritha Bagchi; Luyu Zhang; Wanzhe Zhu; David M. Chambers; Benjamin C. Blount; Víctor R. De Jesús (Environmental Science and Pollution Research, 2021)

Comparing the Biogeochemistry of Storm Surge Sediments and Pre-storm Soils in Coastal Wetlands: Hurricane Irma and the Florida Everglades - Joshua L. Breithaupt; Nia Hurst; Havalend E. Steinmuller; Evan Duga; Joseph M. Smoak; John S. Kominoski; Lisa G. Chambers (Estuaries and Coasts, 2020)

Coastal Sea Level and Related Fields from Existing Observing Systems - Marta Marcos; Guy Wöppelmann; Andrew Matthews; Rui M. Ponte; Florence Birol; Fabrice Ardhuin; Giovanni Coco; Alvaro Santamaría-Gómez; Valerie Ballu; Laurent Testut; Don Chambers; Justin E. Stopa (Surveys in Geophysics, 2019)

Precipitation mediates sap flux sensitivity to evaporative demand in the neotropics - Charlotte Grossiord; Bradley Christoffersen; Aura M. Alonso-Rodríguez; Kristina Anderson-Teixeira; Heidi Asbjornsen; Luiza Maria T. Aparecido; Z. Carter Berry; Christopher Baraloto; Damien Bonal; Isaac Borrego; Benoit Burban; Jeffrey Q. Chambers; et al. (Oecologia, 2019)

Application of multi-dimensional electrical resistivity tomography datasets to investigate a very slow-moving landslide near Ashcroft, British Columbia, Canada - D. Huntley; P. Bobrowsky; M. Hendry; R. Macciotta; D. Elwood; K. Sattler; M. Best; J. Chambers; P. Meldrum (Landslides, 2019)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Inhibition and decision-processing speed are associated with performance on dynamic posturography in older adults - Mark S. Redfern; April J. Chambers; Patrick J. Sparto; Joseph M. Furman; J. Richard Jennings (Experimental Brain Research, 2019)

A test of top-down control on plant production and nutrient quality in low-salinity tidal marshes - Lori A. Sutter; Randy M. Chambers; Madeline Karp; James E. Perry (Aquatic Sciences, 2019)

Evaluating centralized technical assistance as an implementation strategy to improve cancer prevention and control - Sarah Moreland-Russell; Prajakta Adsul; Seif Nasir; Maria E. Fernandez; Timothy J. Walker; Heather M. Brandt; Robin C. Vanderpool; Meagan Pilar; Paula Cuccaro; Wynne E. Norton; Cynthia A. Vinson; David A. Chambers; et al. (Cancer Causes & Control, 2018)

Bone marrow-derived stem/stromal cells (BMSC) 3D microtissues cultured in BMP-2 supplemented osteogenic induction medium are prone to adipogenesis - K. Futrega; E. Mosaad; K. Chambers; W. B. Lott; J. Clements; M. R. Doran (Cell and Tissue Research, 2018)

Windthrows control biomass patterns and functional composition of Amazon forests - Daniel Magnabosco Marra; Susan E. Trumbore; Niro Higuchi; Gabriel H. P. M. Ribeiro; Robinson I. Negrón‐Juárez; Frederic Holzwarth; Sami W. Rifai; Joaquim dos Santos; Adriano J. N. Lima; Valdely F. Kinupp; Jeffrey Q. Chambers; Christian Wirth (Global Change Biology, 2018)
Amazon forests account for ~25% of global land biomass and tropical tree species. In these forests, windthrows (i.e., snapped and uprooted trees) are a major natural disturbance, but the rates and mechanisms of recovery are not known. To provide a predictive framework for understanding the effects of windthrows on forest structure and functional composition (DBH ≥10 cm), we quantified biomass recovery as a function of windthrow severity (i.e., fraction of windthrow tree mortality on Landsat pixels, ranging from 0%–70%) and time since disturbance for terra‐firme forests in the Central Amazon. Forest monitoring allowed insights into the processes and mechanisms driving the net biomass change (i.e., increment minus loss) and shifts in functional composition. Windthrown areas recovering for between 4–27 years had biomass stocks as low as 65.2–91.7 Mg/ha or 23%–38% of those in nearby undisturbed forests (~255.6 Mg/ha, all sites). Even low windthrow severities (4%–20% tree mortality) caused decadal changes in biomass stocks and structure. While rates of biomass increment in recovering vegetation were nearly double (6.3 ± 1.4 Mg ha − 1 year − 1 ) those of undisturbed forests (~3.7 Mg ha − 1 year − 1 ), biomass loss due to post‐windthrow mortality was high (up to −7.5 ± 8.7 Mg ha − 1 year − 1 , 8.5 years since disturbance) and unpredictable. Consequently, recovery to 90% of “pre‐disturbance” biomass takes up to 40 years. Resprouting trees contributed little to biomass recovery. Instead, light‐demanding, low‐density genera (e.g., Cecropia , Inga , Miconia, Pourouma, Tachigali, and Tapirira ) were favored, resulting in substantial post‐windthrow species turnover. Shifts in functional composition demonstrate that windthrows affect the resilience of live tree biomass by favoring soft‐wooded species with shorter life spans that are more vulnerable to future disturbances. As the time required for forests to recover biomass is likely similar to the recurrence interval of windthrows triggering succession, windthrows have the potential to control landscape biomass/carbon dynamics and functional composition in Amazon forests.

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

Rheological properties of clayey soils originating from flow-like landslides - S. R. Carrière; D. Jongmans; G. Chambon; G. Bièvre; B. Lanson; L. Bertello; M. Berti; M. Jaboyedoff; J.-P. Malet; J. E. Chambers (Landslides, 2018)

Arrowhead (Sagittaria cuneata) as a bioindicator of nitrogen and phosphorus for prairie streams and wetlands - Katherine M. Standen; Patricia A. Chambers; Joseph M. Culp (Wetlands Ecology and Management, 2018)
The emergent aquatic plant, Sagittaria cuneata, is an easily-identified and commonly-found species in the Great Plains region of North America and has the potential to be a bioindicator of nitrogen (N) and phosphorus (P) because of its previously-identified leaf plasticity in response to nutrient conditions. To identify associations between leaf morphology and soil and water nutrients, we conducted: (1) a 10-week controlled experiment in which plants were grown in nutrient-enriched sediment, nutrient-enriched water, or unamended control trials, and (2) a field study where emergent leaves were collected from 15 streams of varying nutrient concentrations. Plants grown in experimentally enriched sediment were more productive than those grown in enriched water or control conditions: they produced more emergent leaves and tubers, had a larger final biomass and height, and developed emergent leaves that showed a consistent increase in size and unique change in shape over time. Emergent leaves collected from field plants also showed significant variability of leaf traits; however, this variability occurred at all scales of replication (leaf, plant, quadrat, and site), with linear mixed effects modelling indicating that random chance was likely driving this variability. Although sediment nutrients were crucial to successful growth of S. cuneata under controlled conditions, the high variability in leaf morphology under field conditions (likely due to large natural variability at the species, population, and individual scale) make leaf plasticity of S. cuneata unsuitable as a bioindicator. Our results emphasize the need to quantify within and among plant variation in leaf morphology (and to clarify sampling methods) for the many taxa of aquatic macrophytes that are phenotypically plastic and notoriously difficult to classify.

Impacts of Invasive Phragmites australis on Diamondback Terrapin Nesting in Chesapeake Bay - Cassandra E. Cook; Allison M. McCluskey; Randolph M. Chambers (Estuaries and Coasts, 2018)

Plants in aquatic ecosystems: current trends and future directions - Matthew T. O’Hare; Francisca C. Aguiar; Takashi Asaeda; Elisabeth S. Bakker; Patricia A. Chambers; John S. Clayton; Arnaud Elger; Teresa M. Ferreira; Elisabeth M. Gross; Iain D. M. Gunn; Angela M. Gurnell; Seppo Hellsten; et al. (Hydrobiologia, 2018)

A novel citrus viroid found in Australia, tentatively named citrus viroid VII - G. A. Chambers; N. J. Donovan; S. Bodaghi; S. M. Jelinek; G. Vidalakis (Archives of Virology, 2018)

Experiments with By-Catch Reduction Devices to Exclude Diamondback Terrapins and Retain Blue Crabs - Andrew D. Corso; Jacqueline C. Huettenmoser; Olivia R. Trani; Kory Angstadt; Donna Marie Bilkovic; Kirk J. Havens; Timothy M. Russell; David Stanhope; Randolph M. Chambers (Estuaries and Coasts, 2017)

Sensory and motoric influences on attention dynamics during standing balance recovery in young and older adults - Mark S. Redfern; April J. Chambers; J. Richard Jennings; Joseph M. Furman (Experimental Brain Research, 2017)

Global variation in the beta diversity of lake macrophytes is driven by environmental heterogeneity rather than latitude - Janne Alahuhta; Sarian Kosten; Munemitsu Akasaka; Dominique Auderset; Mattia M. Azzella; Rossano Bolpagni; Claudia P. Bove; Patricia A. Chambers; Eglantine Chappuis; John Clayton; Mary de Winton; Frauke Ecke; et al. (Journal of Biogeography, 2017)
Aim We studied global variation in beta diversity patterns of lake macrophytes using regional data from across the world. Specifically, we examined (1) how beta diversity of aquatic macrophytes is partitioned between species turnover and nestedness within each study region, and (2) which environmental characteristics structure variation in these beta diversity components. Location Global. Methods We used presence–absence data for aquatic macrophytes from 21 regions distributed around the world. We calculated pairwise‐site and multiple‐site beta diversity among lakes within each region using Sørensen dissimilarity index and partitioned it into turnover and nestedness coefficients. Beta regression was used to correlate the diversity coefficients with regional environmental characteristics. Results Aquatic macrophytes showed different levels of beta diversity within each of the 21 study regions, with species turnover typically accounting for the majority of beta diversity, especially in high‐diversity regions. However, nestedness contributed 30–50% of total variation in macrophyte beta diversity in low‐diversity regions. The most important environmental factor explaining the three beta diversity coefficients (total, species turnover and nestedness) was elevation range, followed by relative areal extent of freshwater, latitude and water alkalinity range. Main conclusions Our findings show that global patterns in beta diversity of lake macrophytes are caused by species turnover rather than by nestedness. These patterns in beta diversity were driven by natural environmental heterogeneity, notably variability in elevation range (also related to temperature variation) among regions. In addition, a greater range in alkalinity within a region, likely amplified by human activities, was also correlated with increased macrophyte beta diversity. These findings suggest that efforts to conserve aquatic macrophyte diversity should primarily focus on regions with large numbers of lakes that exhibit broad environmental gradients.

Landscape genetics structure of European sweet chestnut (Castanea sativa Mill): indications for conservation priorities - Claudia Mattioni; M. Angela Martin; Francesca Chiocchini; Marcello Cherubini; Muriel Gaudet; Paola Pollegioni; Ivaylo Velichkov; Rob Jarman; Frank M. Chambers; Ladislave Paule; Vasilica L. Damian; Ghiţă C. Crainic; et al. (Tree Genetics & Genomes, 2017)

Riparian vegetation condition is associated with invertebrate assemblage composition in intermittent and humic streams - P. O’Toole; B. J. Robson; J. M. Chambers (Aquatic Sciences, 2017)

Native submerged macrophyte distribution in seasonally-flowing, south-western Australian streams in relation to stream condition - Robyn L. Paice; Jane M. Chambers; Belinda J. Robson (Aquatic Sciences, 2017)

Toward early estimation and treatment of addiction vulnerability: radial arm maze and N-acetyl cysteine before cocaine sensitization or nicotine self-administration in neonatal ventral hippocampal lesion rats - Kalyan N. Rao; Alena M. Sentir; Eric A. Engleman; Richard L. Bell; Leslie A. Hulvershorn; Alan Breier; R. Andrew Chambers (Psychopharmacology, 2016)

Understanding marine dissolved organic matter production: Compositional insights from axenic cultures of Thalassiosira pseudonana - Emily M. Saad; Amelia F. Longo; Luke R. Chambers; Rixiang Huang; Claudia Benitez‐Nelson; Sonya T. Dyhrman; Julia M. Diaz; Yuanzhi Tang; Ellery D. Ingall (Limnology and Oceanography, 2016)

Outcomes of submerged macrophyte restoration in a shallow impounded, eutrophic river - Robyn L. Paice; Jane M. Chambers; Belinda J. Robson (Hydrobiologia, 2016)

Primary melanoma tumor inhibits metastasis through alterations in systemic hemostasis - Jennifer M. Kirstein; M. Nicole Hague; Patricia M. McGowan; Alan B. Tuck; Ann F. Chambers (Journal of Molecular Medicine, 2016)

Ex vivo motility in the base of the rabbit caecum and its associated structures: an electrophysiological and spatiotemporal analysis - Corrin Hulls; Roger G. Lentle; Gordon W Reynolds; Patrick W. M. Janssen; Paul Chambers; Clement de Loubens (Journal of Physiology and Biochemistry, 2016)

Cystathionine-γ-lyase gene silencing with siRNA in monocytes/macrophages attenuates inflammation in cecal ligation and puncture-induced sepsis in the mouse - A Badiei; S T Chambers; R R Gaddam; M Bhatia (Journal of Biosciences, 2016)

Adaptive management of marine mega-fauna in a changing climate - Mariana M. P. B. Fuentes; Lynda Chambers; Andrew Chin; Peter Dann; Kirstin Dobbs; Helene Marsh; Elvira S. Poloczanska; Kim Maison; Malcolm Turner; Robert L. Pressey (Mitigation and Adaptation Strategies for Global Change, 2016)

Toward an integrated monitoring framework to assess the effects of tropical forest degradation and recovery on carbon stocks and biodiversity - Mercedes M. C. Bustamante; Iris Roitman; T. Mitchell Aide; Ane Alencar; Liana O. Anderson; Luiz Aragão; Gregory P. Asner; Jos Barlow; Erika Berenguer; Jeffrey Chambers; Marcos H. Costa; Thierry Fanin; et al. (Global Change Biology, 2016)
Tropical forests harbor a significant portion of global biodiversity and are a critical component of the climate system. Reducing deforestation and forest degradation contributes to global climate‐change mitigation efforts, yet emissions and removals from forest dynamics are still poorly quantified. We reviewed the main challenges to estimate changes in carbon stocks and biodiversity due to degradation and recovery of tropical forests, focusing on three main areas: (1) the combination of field surveys and remote sensing; (2) evaluation of biodiversity and carbon values under a unified strategy; and (3) research efforts needed to understand and quantify forest degradation and recovery. The improvement of models and estimates of changes of forest carbon can foster process‐oriented monitoring of forest dynamics, including different variables and using spatially explicit algorithms that account for regional and local differences, such as variation in climate, soil, nutrient content, topography, biodiversity, disturbance history, recovery pathways, and socioeconomic factors. Generating the data for these models requires affordable large‐scale remote‐sensing tools associated with a robust network of field plots that can generate spatially explicit information on a range of variables through time. By combining ecosystem models, multiscale remote sensing, and networks of field plots, we will be able to evaluate forest degradation and recovery and their interactions with biodiversity and carbon cycling. Improving monitoring strategies will allow a better understanding of the role of forest dynamics in climate‐change mitigation, adaptation, and carbon cycle feedbacks, thereby reducing uncertainties in models of the key processes in the carbon cycle, including their impacts on biodiversity, which are fundamental to support forest governance policies, such as Reducing Emissions from Deforestation and Forest Degradation.

Functionally relevant climate variables for arid lands: a climatic water deficit approach for modelling desert shrub distributions - Thomas E. Dilts; Peter J. Weisberg; Camie M. Dencker; Jeanne C. Chambers (Journal of Biogeography, 2015)
Aim We have three goals. (1) To develop a suite of functionally relevant climate variables for modelling vegetation distribution on arid and semi‐arid landscapes of the Great Basin, USA . (2) To compare the predictive power of vegetation distribution models based on mechanistically proximate factors (water deficit variables) and factors that are more mechanistically removed from a plant's use of water (precipitation). (3) To quantify the climate gradients that control shrub distributions in a cold desert environment. Location The central basin and range ecoregion of the western USA (36–42°N). Methods We used a modified Thornthwaite method to derive monthly water balance variables and to depict them using a water balance climograph. Eighteen variables were calculated from the climograph, representing different components of the seasonal water balance. These were used in boosted regression tree models to derive distribution models for 18 desert shrub species. The water balance approach was compared with an approach that used bioclimatic variables derived from the PRISM (Parameter‐elevation Relationships on Independent Slopes Model) climate data. Results The water balance and bioclimatic approaches yielded models with similar performance in predicting the geographical distribution of most shrub species. Cumulative annual climatic water deficit was consistently the most important water balance variable for predicting shrub type distributions, although predictions were improved by the inclusion of variables that describe the seasonal distribution of water balance such as water supply in the spring, fall actual evapotranspiration, monsoonality and summer decline in actual evapotranspiration. Main conclusions The water balance and bioclimatic approaches to species distribution modelling both yielded similar prediction accuracies. However, the water balance approach offers advantages over the bioclimatic approach because it is mechanistically derived to approximate physical processes important for plant growth.

Nicotine effects in adolescence and adulthood on cognition and α4β2-nicotinic receptors in the neonatal ventral hippocampal lesion rat model of schizophrenia - Sarah A. Berg; Alena M. Sentir; Richard L. Bell; Eric A. Engleman; R. Andrew Chambers (Psychopharmacology, 2015)

Mucous contribution to gut nutrient content in American gizzard shad Dorosoma cepedianum - L. L. Holley; M. K. Heidman; R. M. Chambers; S. L. Sanderson (Journal of Fish Biology, 2015)
This study developed and applied an approach to calculate the proportion of fish gut content composed of mucus secreted by the oropharyngeal cavity and gut. The amount of nitrogen in the contents of the foregut (oesophagus and gizzard) and the epibranchial organs of suspension‐feeding American gizzard shad Dorosoma cepedianum was significantly higher than the nitrogen in the homogeneous food source. Using data collected from suspension‐feeding experiments and the nitrogen content of D. cepedianum mucus, a series of equations illustrated that mucus constituted c. 10% of D. cepedianum foregut content and 12% of epibranchial organ content by dry mass. Future quantification of fish feeding selectivity and absorption efficiency can use this approach to take into account the contribution of fish mucus to the nutrients in the gut contents. This study supports the conclusion that suspension‐feeding D. cepedianum in a heterogeneous environment selectively ingest nutrient‐rich particles, even when gut nutrient content is adjusted to take into account the contribution of mucus.

Relationships between molecular bacterial diversity and chemistry of groundwater in the Wairarapa Valley, New Zealand - KA Sirisena; CJ Daughney; M Moreau; KG Ryan; GK Chambers (New Zealand Journal of Marine and Freshwater Research, 2014)
Groundwater plays an important role in New Zealand water supplies and hence monitoring activities are conducted regularly. Most monitoring programmes aim to evaluate groundwater chemistry and almost completely overlook the microbial component in this ecosystem. In our present study, the bacterial community structure of groundwater in the Wairarapa Valley was examined using the terminal restriction fragment length polymorphism (T‐RFLP), and relationships between bacterial community structure and groundwater chemistry, aquifer confinement and groundwater usage were explored. In addition, the results from this study were compared with a previous T‐RFLP survey of the same area in an attempt to detect changes in bacterial community structure over time. The data obtained suggested that bacterial community structure was related to groundwater chemistry, especially to redox conditions. Species composition showed minimal variation over time if groundwater chemistry remained unchanged. These findings reflect the potential of using bacterial communities as biological indicators to evaluate the health of groundwater ecosystems. We suggest that it is important to include this type of broad bacterial diversity assessment criteria into regular groundwater monitoring activities.

Efficiency of bacteriophage therapy against Cronobacter sakazakii in Galleria mellonella (greater wax moth) larvae - Reza Abbasifar; Andrew M. Kropinski; Parviz M. Sabour; James R. Chambers; Joanne MacKinnon; Thomas Malig; Mansel W. Griffiths (Archives of Virology, 2014)

3D ground model development for an active landslide in Lias mudrocks using geophysical, remote sensing and geotechnical methods - A. J. Merritt; J. E. Chambers; W. Murphy; P. B. Wilkinson; L. J. West; D. A. Gunn; P. I. Meldrum; M. Kirkham; N. Dixon (Landslides, 2014)

Effects of watershed land use on sources and nutritional value of particulate organic matter in temperate headwater streams - Yue Han Lu; Elizabeth A. Canuel; James E. Bauer; R. M. Chambers (Aquatic Sciences, 2014)

Consistency of the current global ocean observing systems from an Argo perspective - K. von Schuckmann; J.-B. Sallée; D. Chambers; P.-Y. Le Traon; C. Cabanes; F. Gaillard; S. Speich; M. Hamon (Ocean Science, 2014)
Variations in the world's ocean heat storage and its associated volume changes are a key factor to gauge global warming and to assess the earth's energy and sea level budget. Estimating global ocean heat content (GOHC) and global steric sea level (GSSL) with temperature/salinity data from the Argo network reveals a positive change of 0.5 ± 0.1 W m−2 (applied to the surface area of the ocean) and 0.5 ± 0.1 mm year−1 during the years 2005 to 2012, averaged between 60° S and 60° N and the 10–1500 m depth layer. In this study, we present an intercomparison of three global ocean observing systems: the Argo network, satellite gravimetry from GRACE and satellite altimetry. Their consistency is investigated from an Argo perspective at global and regional scales during the period 2005–2010. Although we can close the recent global ocean sea level budget within uncertainties, sampling inconsistencies need to be corrected for an accurate global budget due to systematic biases in GOHC and GSSL in the Tropical Ocean. Our findings show that the area around the Tropical Asian Archipelago (TAA) is important to closing the global sea level budget on interannual to decadal timescales, pointing out that the steric estimate from Argo is biased low, as the current mapping methods are insufficient to recover the steric signal in the TAA region. Both the large regional variability and the uncertainties in the current observing system prevent us from extracting indirect information regarding deep-ocean changes. This emphasizes the importance of continuing sustained effort in measuring the deep ocean from ship platforms and by beginning a much needed automated deep-Argo network.

Effect of Water Management on Interannual Variation in Bulk Soil Properties from the Eastern Coastal Everglades - R. M. Chambers; R. L. Hatch; T. M. Russell (Wetlands, 2014)

Spotted bat (Euderma maculatum) microsatellite discovery using illumina sequencing - Faith M. Walker; Jeffrey T. Foster; Kevin P. Drees; Carol L. Chambers (Conservation Genetics Resources, 2014)

Laugh yourself to sleep: memory consolidation for humorous information - Alexis M. Chambers; Jessica D. Payne (Experimental Brain Research, 2014)

Brachypodium distachyon Cell Suspension Cultures: Establishment and Utilisation - D. Hunt; J.P. Chambers; A. Behpouri; S.P. Kelly; L. Whelan; M. Pietrzykowska; F. Downey; P.F. McCabe; C.K.-Y. Ng (Cereal Research Communications, 2014)

Tidal Freshwater Marsh Plant Responses to Low Level Salinity Increases - Lori A. Sutter; James E. Perry; Randy M. Chambers (Wetlands, 2014)

Seasonal Variation in Nutrient Export Along Streams in the Northern Great Plains - Julie Corriveau; Patricia A. Chambers; Joseph M. Culp (Water, Air, & Soil Pollution, 2013)

An unusual BRCA mutation distribution in a high risk cancer genetics clinic - Anna C. Nelson-Moseke; Joanne M. Jeter; Haiyan Cui; Denise J. Roe; Setsuko K. Chambers; Christina M. Laukaitis (Familial Cancer, 2013)

Long-term ecological study (palaeoecology) to chronicle habitat degradation and inform conservation ecology: an exemplar from the Brecon Beacons, South Wales - F. M. Chambers; E. W. Cloutman; J. R. G. Daniell; D. Mauquoy; P. S. Jones (Biodiversity and Conservation, 2013)

Effects of the Veterinary Pharmaceutical Salinomycin and its Formulation on the Plant Brassica rapa - V. Furtula; G. L. Stephenson; K. M. Olaveson; P. A. Chambers (Archives of Environmental Contamination and Toxicology, 2012)

Effects of prenatal immune activation and peri-adolescent stress on amphetamine-induced conditioned place preference in the rat - Neil M. Richtand; Rebecca Ahlbrand; Paul S. Horn; Brad Chambers; Jon Davis; Stephen Benoit (Psychopharmacology, 2012)

Inventory and new records of polychaete species from the Cap Bon Peninsula, north-east coast of Tunisia, Western Mediterranean Sea - S. ZAABI; P. GILLET; S. CHAMBERS; A. AFLI; M. BOUMAIZA (Mediterranean Marine Science, 2012)
An inventory of Polychaete species is recorded from the North east coast of Tunisia with an historic review of the previous literature from Tunisian coasts. Altogether 40 families, 146 genera, and 238 species are currently known from the area in which 86 taxa, 4 families (Chrysopetalidae, Pilargidae, Protodrilidae and Saccocirridae) and 40 genera (Saccocirrus, Protodrilus, Parathelepus, Thelepus, Petta, Isolda, Brada, Tharyx, Paraprionospio, Jasmineira, Hypsicomus, Euchone, Pseudobranchiomma, Laonome, Galathowenia, Lugia, Pseudomystides, Protomystides, Pirakia, Mysta, Eurysyllis, Parapionosyllis, Streptosyllis, Paraehlersia, Sigambra, Ancistrosyllis, Kefersteinia, Chrysopetalum, Bhawania, Fimbriosthenelais, Subadyte, Panthalis, Dorvillea, Scalibregma, Paradoneis, Cirrophorus, Metasychis, Websterinereis, Euniphysa and Mastobranchus) are new additions to the Polychaete fauna of Tunisia. The list, which provides a synthesis of the regional taxonomica work, including coastal areas from Sidi Daoud to the area of Menzel Hurr (Cap Bon Peninsula, Western Mediterranean Sea), can serve as a baseline survey for future studies.

Spatiotemporal mapping of ex vivo motility in the caecum of the rabbit - Corrin Hulls; Roger G. Lentle; Clement de Loubens; Patrick W. M. Janssen; Paul Chambers; Kevin J. Stafford (Journal of Comparative Physiology B, 2012)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

A Test of Bycatch Reduction Devices on Commercial Crab Pots in a Tidal Marsh Creek in Virginia - A. Scott Morris; Stephanie M. Wilson; Erik F. Dever; Randolph M. Chambers (Estuaries and Coasts, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Genetic population structure of the ectomycorrhizal fungus Pisolithus microcarpus suggests high gene flow in south-eastern Australia - Catherine J. Hitchcock; Susan M. Chambers; John W. G. Cairney (Mycorrhiza, 2011)

A Contemporary, Sex‐Limited Change in Body Size of an Estuarine Turtle in Response to Commercial Fishing - MATTHEW E. WOLAK; GEORGE W. GILCHRIST; VICTORIA A. RUZICKA; DANIEL M. NALLY; RANDOLPH M. CHAMBERS (Conservation Biology, 2010)
Juvenile growth rate and adult body size are important components of life‐history strategies because of their direct impact on fitness. The diamondback terrapin ( Malaclemys terrapin ) is a sexually dimorphic, long‐lived turtle inhabiting brackish waters throughout the Atlantic and Gulf coasts of the United States. In parts of its range, terrapins face anthropogenically imposed mortality: juveniles of both sexes inadvertently enter commercial crab traps and drown. For adult females, the carapace eventually grows large enough that they cannot enter traps, whereas males almost never reach that critical size. We compared age structure, carapace dimensions, growth curves, and indices of sexual dimorphism for a Chesapeake Bay population of terrapins (where mortality of turtles is high due to crab traps) with contemporary terrapins from Long Island Sound and museum specimens from Chesapeake Bay (neither group subject to commercial crab traps). We also calculated the allochronic and synchronic rates of evolutionary change (haldanes) for males and females to measure the rate of trait change in a population or between populations, respectively. We found a dramatic shift to a younger male age structure, a decrease in the length of time to terminal female carapace size, a 15% increase in female carapace width, and an increase in sexual dimorphism in Chesapeake Bay. In a new twist, our results implicate a fishery in the selective increase in size of a reptilian bycatch species. These sex‐specific changes in life history and demography have implications for population viability that need to be considered when addressing conservation of this threatened turtle.

Ventral and dorsal striatal dopamine efflux and behavior in rats with simple vs. co-morbid histories of cocaine sensitization and neonatal ventral hippocampal lesions - Robert Andrew Chambers; Alena M. Sentir; Eric A. Engleman (Psychopharmacology, 2010)

Conservation Genetics - Steven M. Chambers (Conservation Biology, 2010)

Lack of intermediate‐scale disturbance data prevents robust extrapolation of plot‐level tree mortality rates for old‐growth tropical forests - Jeffrey Q. Chambers; Robinson I. Negrón‐Juárez; George C. Hurtt; Daniel M. Marra; Niro Higuchi (Ecology Letters, 2009)
Ecology Letters (2009) 12: E22–E25 Abstract Lloyd et al. (2009) question the methods, concepts and conclusions of Fisher et al. (2008) . We address these assertions, and place our work into a broader context. We demonstrate the veracity of Fisher et al. , and further show that lack of data for intermediate‐scale tree mortality disturbance events for old‐growth tropical forests might prevent robust extrapolation of forest plot biomass accumulation data, and accurate estimates of distribution parameters such as power‐law exponents ( α ).

Linking past cultural developments to palaeoenvironmental changes in Estonia - Ülle Sillasoo; Anneli Poska; Heikki Seppä; Maarten Blaauw; Frank M. Chambers (Vegetation History and Archaeobotany, 2009)

Immunological cost of chemical defence and the evolution of herbivore diet breadth - Angela M. Smilanich; Lee A. Dyer; Jeffrey Q. Chambers; M. Deane Bowers (Ecology Letters, 2009)
Selective pressures from host plant chemistry and natural enemies may contribute independently to driving insect herbivores towards narrow diet breadths. We used the specialist caterpillar, Junonia coenia (Nymphalidae), which sequesters defensive compounds, iridoid glycosides, from its host plants to assess the effects of plant chemistry and sequestration on the larval immune response. A series of experiments using implanted glass beads to challenge immune function showed that larvae feeding on diets with high concentrations of iridoid glycosides are more likely to have their immune response compromised than those feeding on diets low in these compounds. These results indicate that larvae feeding on plants with high concentrations of toxins might be more poorly defended against parasitoids, while at the same time being better defended against predators, suggesting that predators and parasitoids can exert different selective pressures on the evolution of herbivore diet breadth.

Hyperspectral remote detection of niche partitioning among canopy trees driven by blowdown gap disturbances in the Central Amazon - Jeffrey Q. Chambers; Amanda L. Robertson; Vilany M. C. Carneiro; Adriano J. N. Lima; Marie-Louise Smith; Lucie C. Plourde; Niro Higuchi (Oecologia, 2009)

Comprehensive assessment of carbon productivity, allocation and storage in three Amazonian forests - YADVINDER MALHI; LUIZ EDUARDO O. C. ARAGÃO; DANIEL B. METCALFE; ROMILDA PAIVA; CARLOS A. QUESADA; SAMUEL ALMEIDA; LIANA ANDERSON; PAULO BRANDO; JEFFREY Q. CHAMBERS; ANTONIO C. L. Da COSTA; LUCY R. HUTYRA; PAULO OLIVEIRA; et al. (Global Change Biology, 2009)
The allocation and cycling of carbon (C) within forests is an important component of the biospheric C cycle, but is particularly understudied within tropical forests. We synthesise reported and unpublished results from three lowland rainforest sites in Amazonia (in the regions of Manaus, Tapajós and Caxiuanã), all major sites of the Large‐Scale Biosphere–Atmosphere Programme (LBA). We attempt a comprehensive synthesis of the C stocks, nutrient status and, particularly, the allocation and internal C dynamics of all three sites. The calculated net primary productivities (NPP) are 10.1±1.4 Mg C ha −1 yr −1 (Manaus), 14.4±1.3 Mg C ha −1 yr −1 (Tapajós) and 10.0±1.2 Mg C ha −1 yr −1 (Caxiuanã). All errors bars report standard errors. Soil and leaf nutrient analyses indicate that Tapajós has significantly more plant‐available phosphorus and calcium. Autotrophic respiration at all three sites (14.9–21.4 Mg C ha yr −1 ) is more challenging to measure, with the largest component and greatest source of uncertainty being leaf dark respiration. Comparison of measured soil respiration with that predicted from C cycling measurements provides an independent constraint. It shows general good agreement at all three sites, with perhaps some evidence for measured soil respiration being less than expected. Twenty to thirty percent of fixed C is allocated belowground. Comparison of gross primary productivity (GPP), derived from ecosystem flux measurements with that derived from component studies (NPP plus autotrophic respiration) provides an additional crosscheck. The two approaches are in good agreement, giving increased confidence in both approaches to estimating GPP. The ecosystem carbon‐use efficiency (CUEs), the ratio of NPP to GPP, is similar at Manaus (0.34±0.10) and Caxiuanã (0.32±0.07), but may be higher at Tapajós (0.49±0.16), although the difference is not significant. Old growth or infertile tropical forests may have low CUE compared with recently disturbed and/or fertile forests.

Effect of anti-fibrinolytic therapy on experimental melanoma metastasis - Jennifer M. Kirstein; Kevin C. Graham; Lisa T. MacKenzie; Danielle E. Johnston; Leslie J. Martin; Alan B. Tuck; Ian C. MacDonald; Ann F. Chambers (Clinical & Experimental Metastasis, 2009)

Common reed Phragmites australis occurrence and adjacent land use along estuarine shoreline in Chesapeake Bay - Randolph M. Chambers; Kirk J. Havens; Sharon Killeen; Marcia Berman (Wetlands, 2008)

High-definition spatiotemporal mapping of contractile activity in the isolated proximal colon of the rabbit - Roger G. Lentle; Patrick W. M. Janssen; Patchana Asvarujanon; Paul Chambers; Kevin J. Stafford; Yacine Hemar (Journal of Comparative Physiology B, 2008)

Global diversity of aquatic macrophytes in freshwater - P. A. Chambers; P. Lacoul; K. J. Murphy; S. M. Thomaz (Hydrobiologia, 2008)

2-Aminopyridine—a label for bridging of oligosaccharides HPLC profiling and glycoarray printing - N. V. Shilova; O. E. Galanina; A. Yu. Rubina; V. I. Butvilovskaya; M. E. Huflejt; J. Chambers; A. Roucoux; N. V. Bovin (Glycoconjugate Journal, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Recent vegetation history of Drygarn Fawr (Elenydd SSSI), Cambrian Mountains, Wales: implications for conservation management of degraded blanket mires - F. M. Chambers; D. Mauquoy; E. W. Cloutman; J. R. G. Daniell; P. S. Jones (Biodiversity and Conservation, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

High definition mapping of circular and longitudinal motility in the terminal ileum of the brushtail possum Trichosurus vulpecula with watery and viscous perfusates - Roger G. Lentle; Patrick W. M. Janssen; Patchana Asvarujanon; Paul Chambers; Kevin J. Stafford; Yacine Hemar (Journal of Comparative Physiology B, 2007)

Genetic variation in island populations of tuatara (Sphenodon spp) inferred from microsatellite markers - Elizabeth S. MacAvoy; Lorna M. McGibbon; James P. Sainsbury; Hayley Lawrence; Carol A. Wilson; Charles H. Daugherty; Geoffrey K. Chambers (Conservation Genetics, 2007)

Ecological regime shifts in salinised wetland systems. I. Salinity thresholds for the loss of submerged macrophytes - Lien L. Sim; Jane M. Chambers; Jenny A. Davis (Hydrobiologia, 2006)

Ecological regime shifts in salinised wetland systems. II. Factors affecting the dominance of benthic microbial communities - Lien L. Sim; Jenny A. Davis; Jane M. Chambers (Hydrobiologia, 2006)

Distribution and nutrient status of haplotypes of the marsh grassPhragmites australis along the Rappahannock River in Virginia - C. Rebekah Packett; Randolph M. Chambers (Estuaries and Coasts, 2006)

Taxonomic Considerations in Listing Subspecies Under the U.S. Endangered Species Act - SUSAN M. HAIG; ERIK A. BEEVER; STEVEN M. CHAMBERS; HOPE M. DRAHEIM; BRUCE D. DUGGER; SUSIE DUNHAM; ELISE ELLIOTT‐SMITH; JOSEPH B. FONTAINE; DYLAN C. KESLER; BRIAN J. KNAUS; IARA F. LOPES; PETE LOSCHL; et al. (Conservation Biology, 2006)
The U.S. Endangered Species Act (ESA) allows listing of subspecies and other groupings below the rank of species. This provides the U.S. Fish and Wildlife Service and the National Marine Fisheries Service with a means to target the most critical unit in need of conservation. Although roughly one‐quarter of listed taxa are subspecies, these management agencies are hindered by uncertainties about taxonomic standards during listing or delisting activities. In a review of taxonomic publications and societies, we found few subspecies lists and none that stated standardized criteria for determining subspecific taxa. Lack of criteria is attributed to a centuries‐old debate over species and subspecies concepts. Nevertheless, the critical need to resolve this debate for ESA listings led us to propose that minimal biological criteria to define disjunct subspecies (legally or taxonomically) should include the discreteness and significance criteria of distinct population segments (as defined under the ESA). Our subspecies criteria are in stark contrast to that proposed by supporters of the phylogenetic species concept and provide a clear distinction between species and subspecies. Efforts to eliminate or reduce ambiguity associated with subspecies‐level classifications will assist with ESA listing decisions. Thus, we urge professional taxonomic societies to publish and periodically update peer‐reviewed species and subspecies lists. This effort must be paralleled throughout the world for efficient taxonomic conservation to take place.

Variation in soil phosphorus, sulfur, and iron pools among south Florida wetlands - Randolph M. Chambers; Kristin A. Pederson (Hydrobiologia, 2006)

Molecular analysis of isolates from influenza B outbreaks in the U.S. and Nepal, 2005 - L. T. Daum; L. C. Canas; A. I. Klimov; M. W. Shaw; R. V. Gibbons; S. K. Shrestha; K. S. Myint; R. P. Acharya; N. Rimal; F. Reese; D. M. Niemeyer; B. P. Arulanandam; et al. (Archives of Virology, 2006)

Northern Rivers Ecosystem Initiative: Nutrients and Dissolved Oxygen – Issues and Impacts - Patricia A. Chambers; Joseph M. Culp; Nancy E. Glozier; Kevin J. Cash; Fred J. Wrona; Leigh Noton (Environmental Monitoring and Assessment, 2006)

Changes in Nutrient Loading in an Agricultural Watershed and Its Effects on Water Quality and Stream Biota - P. A. Chambers; R. Meissner; F. J. Wrona; H. Rupp; H. Guhr; J. Seeger; J. M. Culp; R. B. Brua (Hydrobiologia, 2006)

Characterization of variable microsatellite loci in Forbes’ parakeet (Cyanoramphus forbesi) and their use in other parrots - Chi-hang Chan; Kaye N Ballantyne; David M Lambert; Geoffrey K Chambers (Conservation Genetics, 2006)

Natal philopatry does not lead to population genetic differentiation in Buller's albatross ( Thalassarche bulleri bulleri ) - MARGO VAN BEKKUM; PAUL M. SAGAR; JEAN‐CLAUDE STAHL; GEOFFREY K. CHAMBERS (Molecular Ecology, 2006)
Genetic variability in the only two existing populations of Buller's albatross ( Thalassarche bulleri bulleri ) was assessed using six polymorphic microsatellite loci. Large biological samples were obtained from both the Snares ( n = 99) and the Solander Islands ( n = 27). Several measures of genetic differentiation including F ST and R ST and a principal coordinates analysis (PCO) suggest a complete absence of genetic structure between three breeding colonies on the Snares Islands, and between them and one breeding colony on the Solander Islands. Mark/recapture studies of recently banded albatross chicks on the Snares found high natal philopatry in T . b . bulleri , but the microsatellite DNA data suggest that sufficient gene flow still occurs between all four breeding colonies to maintain a genetically homogeneous population overall.

GGM02 – An improved Earth gravity field model from GRACE - B. Tapley; J. Ries; S. Bettadpur; D. Chambers; M. Cheng; F. Condi; B. Gunter; Z. Kang; P. Nagel; R. Pastor; T. Pekker; S. Poole; et al. (Journal of Geodesy, 2005)

Tree allometry and improved estimation of carbon stocks and balance in tropical forests - J. Chave; C. Andalo; S. Brown; M. A. Cairns; J. Q. Chambers; D. Eamus; H. Fölster; F. Fromard; N. Higuchi; T. Kira; J.-P. Lescure; B. W. Nelson; et al. (Oecologia, 2005)

Change in mean temperature as a predictor of extreme temperature change in the Asia–Pacific region - G. M. Griffiths; L. E. Chambers; M. R. Haylock; M. J. Manton; N. Nicholls; H.‐J. Baek; Y. Choi; P. M. Della‐Marta; A. Gosai; N. Iga; R. Lata; V. Laurent; et al. (International Journal of Climatology, 2005)
Trends (1961–2003) in daily maximum and minimum temperatures, extremes and variance were found to be spatially coherent across the Asia–Pacific region. The majority of stations exhibited significant trends: increases in mean maximum and mean minimum temperature, decreases in cold nights and cool days, and increases in warm nights. No station showed a significant increase in cold days or cold nights, but a few sites showed significant decreases in hot days and warm nights. Significant decreases were observed in both maximum and minimum temperature standard deviation in China, Korea and some stations in Japan (probably reflecting urbanization effects), but also for some Thailand and coastal Australian sites. The South Pacific convergence zone (SPCZ) region between Fiji and the Solomon Islands showed a significant increase in maximum temperature variability. Correlations between mean temperature and the frequency of extreme temperatures were strongest in the tropical Pacific Ocean from French Polynesia to Papua New Guinea, Malaysia, the Philippines, Thailand and southern Japan. Correlations were weaker at continental or higher latitude locations, which may partly reflect urbanization. For non‐urban stations, the dominant distribution change for both maximum and minimum temperature involved a change in the mean, impacting on one or both extremes, with no change in standard deviation. This occurred from French Polynesia to Papua New Guinea (except for maximum temperature changes near the SPCZ), in Malaysia, the Philippines, and several outlying Japanese islands. For urbanized stations the dominant change was a change in the mean and variance, impacting on one or both extremes. This result was particularly evident for minimum temperature. The results presented here, for non‐urban tropical and maritime locations in the Asia–Pacific region, support the hypothesis that changes in mean temperature may be used to predict changes in extreme temperatures. At urbanized or higher latitude locations, changes in variance should be incorporated. Copyright © 2005 Royal Meteorological Society.

Natural reward-related learning in rats with neonatal ventral hippocampal lesions and prior cocaine exposure - R. Andrew Chambers; Rachel M. Jones; Scott Brown; Jane R. Taylor (Psychopharmacology, 2005)

Biomass change in an Atlantic tropical moist forest: the ENSO effect in permanent sample plots over a 22-year period - Samir G. Rolim; Renato M. Jesus; Henrique E. M. Nascimento; Hilton T. Z. do Couto; Jeffrey Q. Chambers (Oecologia, 2005)

Response of tree biomass and wood litter to disturbance in a Central Amazon forest - Jeffrey Q. Chambers; Niro Higuchi; Liliane M. Teixeira; Joaquim dos Santos; Susan G. Laurance; Susan E. Trumbore (Oecologia, 2004)

Utilisation of carbon substrates by multiple genotypes of ericoid mycorrhizal fungal endophytes from eastern Australian Ericaceae - David J. Midgley; Susan M. Chambers; John W. G. Cairney (Mycorrhiza, 2004)

Distribution of ericoid mycorrhizal endophytes and root-associated fungi in neighbouring Ericaceae plants in the field - David J. Midgley; Susan M. Chambers; John W.G. Cairney (Plant and Soil, 2004)

Variation in nitrogen source utilisation by nine Amanita muscaria genotypes from Australian Pinus radiata plantations - Nicole A. Sawyer; Susan M. Chambers; John W. G. Cairney (Mycorrhiza, 2003)

Cultures of equine respiratory epithelial cells and organ explants as tools for the study of equine influenza virus infection - C. Lin; R. E. Holland Jr; N. M. Williams; T. M. Chambers (Archives of Virology, 2001)

Biogeochemical effects of iron availability on primary producers in a shallow marine carbonate environment - Randolph M. Chambers; James W. Fourqurean; Stephen A. Macko; Regis Hoppenot (Limnology and Oceanography, 2001)
We completed a synoptic survey of iron, phosphorus, and sulfur concentrations in shallow marine carbonate sediments from south Florida. Total extracted iron concentrations typically were −1 dry weight (DW) and tended to decrease away from the Florida mainland, whereas total extracted phosphorus concentrations mostly were −1 DW and tended to decrease from west to east across Florida Bay. Concentrations of reduced sulfur compounds, up to 40 µmol g −1 DW, tended to covary with sediment iron concentrations, suggesting that sulfide mineral formation was ironߚlimited. An index of iron availability derived from sediment data was negatively correlated with chlorophyll a concentrations in surface waters, demonstrating the close coupling of sedimentߚwater column processes. Eight months after applying a surface layer of iron oxide granules to experimental plots, sediment iron, phosphorus, and sulfur were elevated to a depth of 10 cm relative to control plots. Biomass of the seagrass Thalassia testudinum was not different between control and iron addition plots, but individual shoot growth rates were significantly higher in experimental plots after 8 months. Although the iron content of leaf tissues was significantly higher from iron addition plots, no difference in phosphorus content of T. testudinum leaves was observed. Iron addition altered plant exposure to free sulfide, documented by a significantly higher d34S of leaf tissue from experimental plots relative to controls. Iron as a buffer to toxic sulfides may promote individual shoot growth, but phosphorus availability to plants still appears to limit production in carbonate sediments.

Diverged evolution of recent equine-2 influenza (H3N8) viruses in the Western Hemisphere - A. C. K. Lai; T. M. Chambers; R. E. Holland, Jr.; P. S. Morley; D. M. Haines; H. G. G. Townsend; M. Barrandeguy (Archives of Virology, 2001)

Variation in nitrogen source utilisation by Pisolithus isolates maintained in axenic culture - Ian C. Anderson; Susan M. Chambers; J. W. G. Cairney (Mycorrhiza, 2001)

Mid‐ and late‐Holocene climatic changes: a test of periodicity and solar forcing in proxy‐climate data from blanket peat bogs - Frank M. Chambers; Jeffrey J. Blackford (Journal of Quaternary Science, 2001)
A wide range of palaeoenvironmental evidence from the Holocene has suggested periodicities in the Earth's climate of 10s to 1000s of years. Identifying these millennial‐, century‐ and decadal periodicities, and their impacts, is critical in developing a fuller understanding of natural climate variability. Any solar‐induced climatic change needs to be distinguished from other causes of natural climate variability and from short‐term catastrophic events induced either by external or internal processes. Such events might themselves generate a periodicity, or in combination with other forcing factors they may contribute towards a periodicity (and so spuriously imply a universal and continuing periodicity in the climate record), or they may resonate with a solar‐induced periodicity. Here, evidence from peat records for periodicity in climate change over the mid to late Holocene is reviewed and this is followed by a test of the replicability of claimed periodicities using blanket peat data covering the past 2000 yr from four sites in the British Isles. Results suggest that the mires studied do go through phases of being responsive to periodic forcing factors, with ca. 200, ca. 80 and 60–50 yr wavelengths reflected in some data sets. However, the patterns shown are not consistent. This could be the result of local conditions at individual mires (human impact, sensitivity and vegetation succession) or of changes in the strength or nature of global forcing factors. Assessing a solar–mire link remains difficult because the century‐scale variations of the Sun show different intervals between solar minima, the durations of which are themselves unequal, and because the proxy‐climate data‐sets from peat profiles may themselves not be dated with sufficient precision and/or accuracy. Copyright © 2001 John Wiley & Sons, Ltd.

Soil-plant relations along a soil-water gradient in great basin riparian meadows - Regine M. Castelli; Jeanne C. Chambers; Robin J. Tausch (Wetlands, 2000)

A study of the impacts of Zn and Cu on two rhizobial species in soils of a long-term field experiment - Amar M. Chaudri; Céline M. G. Allain; Vera L. Barbosa-Jefferson; Fiona A. Nicholson; Brian J. Chambers; Steve P. McGrath (Plant and Soil, 2000)

Decomposition and carbon cycling of dead trees in tropical forests of the central Amazon - J. Q. Chambers; N. Higuchi; J. P. Schimel; L. V. Ferreira; J. M. Melack (Oecologia, 2000)

Gas exchange and heart rate in the harbour porpoise, Phocoena phocoena - J. Z. Reed; C. Chambers; C. J. Hunter; C. Lockyer; R. Kastelein; M. A. Fedak; R. G. Boutilier (Journal of Comparative Physiology B, 2000)

Selective destruction of brain serotonin neurons by 5,7-dihydroxytryptamine increases responding for a conditioned reward - P. J. Fletcher; Karin M. Korth; John W. Chambers (Psychopharmacology, 1999)

Depletion of brain serotonin following intra-raphe injections - P. J. Fletcher; Karin M. Korth; John W. Chambers (Psychopharmacology, 1999)

Molecular identification of co-occurring Cortinarius and Dermocybe species from southeastern Australian sclerophyll forests - S. M. Chambers; N. A. Sawyer; J. W. G. Cairney (Mycorrhiza, 1999)

The Effects of Phragmites Removal on Nutrient Pools in a Freshwater Tidal Marsh Ecosystem - Laura A. Meyerson; Randolph M. Chambers; Kristiina A. Vogt (Biological Invasions, 1999)

Comment on D. M. Wilkinson (1997). ‘Plant colonization: are wind dispersed seeds really dispersed by birds at larger spatial and temporal scales?’ - F. M. Chambers (Journal of Biogeography, 1999)

Utilisation of organic nitrogen and phosphorus sources by mycorrhizal endophytes of Woollsia pungens (Cav.) F. Muell. (Epacridaceae) - A. Chen; S. M. Chambers; J. W. G. Cairney (Mycorrhiza, 1999)

Grasshopper response to a 40-year experimental burning and mowing regime, with recommendations for invertebrate conservation management - B. Q. Chambers; M. J. Samways (Biodiversity and Conservation, 1998)

Towards a molecular identification of the Pisonia mycobiont - S. M. Chambers; J. M. Sharples; J. W. G. Cairney (Mycorrhiza, 1998)

Interactions between Pisolithus tinctorius and its hosts: a review of current knowledge - J. W. G. Cairney; S. M. Chambers (Mycorrhiza, 1997)

Porewater chemistry associated withPhragmites andSpartina in a Connecticut tidal marsh - Randolph M. Chambers (Wetlands, 1997)

Dating prehistoric bog‐fires in northern England to calendar years by long‐distance cross‐matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)

Dating prehistoric bog-fires in northern England to calendar years by long-distance cross-matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)

The biology of the predatory miteHypoaspis miles (Acari: Laelapidae), a potential biological control agent ofBradysia paupera (Dipt.: Sciaridae) - E. M. Wright; R. J. Chambers (BioControl, 1994)

Adaptation and serial passage of porcine group C rotavirus in ST-cells, an established diploid swine testicular cell line - M. W. Welter; C. J. Welter; D. M. Chambers; L. Svensson (Archives of Virology, 1991)

Influenza viral infection of swine in the United States 1988?1989 - T. M. Chambers; Virginia S. Hinshaw; Y. Kawaoka; B. C. Easterday; R. G. Webster (Archives of Virology, 1991)

Structural analysis of glycerol-3-phosphate dehydrogenase from severalDrosophila species - G. K. Chambers; A. A. Felton; J. A. M. Ramshaw; D. Larson Rigby; D. T. Sullivan (Biochemical Genetics, 1985)

Structural analysis of glycerol-3-phosphate dehydrogenase from severalDrosophila species - G. K. Chambers; A. A. Felton; J. A. M. Ramshaw; D. Larson Rigby; D. T. Sullivan (Biochemical Genetics, 1985)

A small genetic region that controls dihydroorotate dehydrogenase in Drosophila melanogaster - John M. Rawls; Carol L. Chambers; William S. Cohen (Biochemical Genetics, 1981)

Comparative life history and respiratory activity of “wild” and colonized Caribbean fruit flies [Dipt.: Tephritidae] - N. C. Leppla; M. D. Huettel; D. L. Chambers; W. K. Turner (BioControl, 1976)

Rearing and life history studies onBiosteres (Opius) longicaudatus [Hym.: Braconidae] - P. D. Greany; T. R. Ashley; R. M. Baranowski; D. L. Chambers (BioControl, 1976)